A comparative study on pure and cobalt doped manganese ferrite (Co: MnFe2O4) nanoparticles in their optical, structural, and gas sensing properties. (November 2021) - D, Deivatamil; M, John Abel; P, Nancy Dyana; R, Thiruneelakandan; J, Joseph Prince
Abstract: NH3 is a type of foul smelling gas, when breathed beyond a comfortable level, is extremely hazardous to human health. Developing of room-temperature ammonia sensors are one of the challenging task in research. Manganese ferrites and cobalt doped manganese ferrites nanoparticles were successfully produced in this work, and used as a sensing material for ammonia gas sensor, also getting the better results at room temperature. The synthesized materials were confirmed by various characterization techniques namely XRD, SEM & EDAX, FTIR, and DRS. Three different weight percentage (1, 3, and 5 wt%) of Co is doped with MnFe2 O4 nanomaterial and study the optical properties and the ammonia sensing ability comparatively. From that 5 wt% Co: MnFe2 O4 nanoparticles shows good sensing percentage of about 75.3 %. Highlights: The MnFe2 O4 and Co doped MnFe2 O4 are prepared by co-precipitation method. The structural and morphological properties of the nanoparticles were examined. The maximum sensing efficiency was observed for 5 wt% Co doped MnFe2 O4 . The sensing percentage was found to be 75% for 5 wt% Co doped MnFe2 O4 .